2022
DOI: 10.3389/fpsyg.2022.958748
|View full text |Cite
|
Sign up to set email alerts
|

Revealing underlying factors of absenteeism: A machine learning approach

Abstract: IntroductionThe basis of support is understanding. In machine learning, understanding happens through assimilated knowledge and is centered on six pillars: big data, data volume, value, variety, velocity, and veracity. This study analyzes school attendance problems (SAP), which encompasses its legal statutes, school codes, students’ attendance behaviors, and interventions in a school environment. The support pillars include attention to the physical classroom, school climate, and personal underlying factors im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Further, another study showed that training a classifier with 90.2% accuracy using over 20,000 recorded behaviors and identifying peer relationships as an important root cause directly affecting absenteeism is possible. An important finding shows empirical support for the fundamental idea that peer relationships are a significant absenteeism-influencing factor (Bowen, 2022). It means teachers cannot force students to change.…”
Section: Described By Teachersmentioning
confidence: 81%
“…Further, another study showed that training a classifier with 90.2% accuracy using over 20,000 recorded behaviors and identifying peer relationships as an important root cause directly affecting absenteeism is possible. An important finding shows empirical support for the fundamental idea that peer relationships are a significant absenteeism-influencing factor (Bowen, 2022). It means teachers cannot force students to change.…”
Section: Described By Teachersmentioning
confidence: 81%
“…In review article, there is the suggestion that engagement with school is augmented by restorative practices, including school-family-community partnerships and strategies to enhance safety and social relationships. Bowen et al (2022) describe a program that leverages technology and a gamification system to engage learners from underserved communities in an intervention that fosters social and emotional qualities for success. The program does not directly address engagement with learning, but it does so indirectly by supporting the development of learner's social and emotional skills and competencies, which the authors associate with in-class participation.…”
Section: Attendance In the Service Of Engagement With Learningmentioning
confidence: 99%
“…In Kearney et al 's (2022) review article, there is the suggestion that engagement with school is augmented by restorative practices, including school-family-community partnerships and strategies to enhance safety and social relationships. Bowen et al (2022) describe a program that leverages technology and a gamification system to engage learners from underserved communities in an intervention that fosters social and emotional qualities for success. The program does not directly address engagement with learning, but it does so indirectly by supporting the development of learner's social and emotional skills and competencies, which the authors associate with in-class participation.…”
Section: Attendance In the Service Of Engagement With Learningmentioning
confidence: 99%